1993
DOI: 10.1002/sia.740201306
|View full text |Cite
|
Sign up to set email alerts
|

GaAs/AlAs superlattice as a proposed new reference material for sputter depth profiling

Abstract: A GaAs/AlAs superlattice growth by metal-organic chemical vapour deposition is being proposed as the single crystalline multilayer reference material for sputter depth profiling. This material was characterized by transmission electron microscopy experiments, which showed that the interface between GaAs and AlAs is atomically flat. The preliminary depth profiling experiments were carried out by AES and SIMS.The AES experiments were performed using a Perkin-Elmer SAM 660 scanning Auger microprobe and the SIMS e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
(1 reference statement)
1
19
0
Order By: Relevance
“…15 The energy dependence of the depth resolution obtained is shown in Fig. 3 with the extrapolation line of Eqn.…”
Section: Resultsmentioning
confidence: 99%
“…15 The energy dependence of the depth resolution obtained is shown in Fig. 3 with the extrapolation line of Eqn.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the dependence of the depth resolution on the primary energy of low-energy ions is one of the most important factors. However, most of the studies were reported for a primary energy of above 500 eV, 16,17 and systematic investigation in the low-energy region of below 500 eV is very limited.…”
Section: Introductionmentioning
confidence: 94%
“…7 The projection range of implanted ions with low energy is smaller than that with high energy. 8 These results suggest that ion bombardment of low energy may cause the lesser the damage to the materials.…”
Section: Introductionmentioning
confidence: 98%